U.S. media coverage of Brittany Maynard's choice to die: how ideology and framing converged. Issue 3 (26th May 2020) - Lauffer, Kimberly; Baker, Sean
ABSTRACT: In 2014 Brittany Maynard, 29, diagnosed with terminal brain cancer, moved from California to Oregon, one of few U.S. states with legal aid in dying, so she could determine when and how she would die. We used theoretical constructs of framing, ideology, and hegemony as we inductively identified frames that emerged from the coverage in prominent U.S. publications and contextualized them within existing hegemonic attitudes. Although news frames initially focused on an event (her decision), they eventually covered thematic issues underlying her decision. Overall, frames reflected existing and changing ideological beliefs about aid in dying.